WHAT DRIVES WOMEN TO BECOME HAMLET'S HEAD? A STUDY OF THE DAYAH BAROE VILLAGE IN ACEH - Masni, Melly; Maghfirah, Arifa (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2023)
This study aims to explore the primary factors that encourage women's participation in village administration and the effect of women's leadership as hamlet chiefs on the government of Dayah Baro Village, Delima District, Pidie Regency. This study employed a qualitative methodology and utilized observation and interviews to collect data. The results of this study indicate that the level of Education and emotional empathy possessed by female hamlet leaders encourage their participation in village administration. Consequently, the effect of women's leadership in government is that they reform the village agenda by implementing numerous women-centered agendas. In addition, their presence in the village government structure correlates positively with increased women's participation in Dayah Baroe Village due to the ease of interaction and the numerous women-based agendas facilitated by the leaders of these women's hamlets.